Effect of Non-Genetic Factors and Temperature-Humidity Index (THI) on Daily Milk Yield of Crossbred Jersey and Holstein Friesian Cows in Chitwan, Nepal - Paudel, Sagar; Bhattarai, Nirajan; Basnet, Hom Bahadur; Amatya Gorkhali, Neena; Sapkota, Saroj; Hamal, Pratik (Journal of Agriculture and Forestry University, 2025)
The effect of non-genetic factors on daily milk yield helps optimize production, improve economic efficiency, make informed management decisions, advance breeding programs, and adapt to changing climatic impacts. The present study had the main objective to assess the effect of temperature-humidity index (THI) and other non-genetic factors including year, season of calving, parity, season of milking, and stage of lactation on daily milk yield (DMY) of Jersey and Holstein-Friesian dairy herd reared under sub-tropical region at National Cattle Research Center (NCRP), Chitwan, Nepal. A total number of 88,268 individual daily milk records maintained under the pedigree performance recording scheme (PPRS) during the year 2016 to 2022 involving 50 to 75 lactating cows (depending upon the factors studied) were used for this study. Data were analyzed using General Linear Model procedure (GLM) using R Program version 4.4.1. Least Squares and Maximum Likelihood Estimation methods with unbalanced subclass numbers were used for the analysis of data. The overall mean daily milk yield (DMY) was 8.09 kg with 7.79 kg for Jersey breed and 8.40 kg for Holstein Friesian (HF) cattle breeds at National Cattle Research Program (NCRP), Chitwan. Primiparous (first parity) cows have highest DMY of 8.55 kg with significantly lower production (7.49 kg/day) for secundiparous (second parity) cows. An overall improvement in DMY was observed across breeds in recent years, likely due to breed improvement programs, although a slight decline was noted during the COVID-19 years (2019 and 2020). Highest DMY was observed during early stage of lactation (10.23 kg) and the month of December to May. Milk yield decreases with increasing THI levels (i.e., as heat stress increases), in both Jersey and Holstein Friesian (HF) breeds. This study revealed that milk yield in Chitwan dairy cows at NCRP farm is significantly influenced by non-genetic factors and thermal stress, with Holstein crosses producing more but being more heat-sensitive, while optimal parity, lactation stage, and cooler seasons enhanced productivity.